2022
DOI: 10.1177/13524585221079744
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory threshold predicts treatment response in relapsing multiple sclerosis

Abstract: Background: Olfactory threshold (OT) is associated with short-term inflammatory activity in relapsing multiple sclerosis (RMS). Objective: We aimed to investigate OT for prediction of treatment response in RMS. Methods: In this 5-year prospective study on 123 RMS patients, OT was measured at disease-modifying treatment (DMT) initiation (M0), after 3 months (M3), and 12 months (M12) by Sniffin’ Sticks test. Primary endpoint was defined as an absence of relapse during the observation period, with Expanded Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…First, we completely agree that OT is indeed a biomarker of disease activity, which has been shown in previous studies. [2][3][4][5] As Santos et al correctly point out, OT scores in the present study significantly differed already at baseline, that is, before disease-modifying therapy (DMT) initiation, between patients with and without treatment response. We also agree that, in line with previous studies, this is in all likelihood explained by the influence of recent disease activity.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 77%
See 2 more Smart Citations
“…First, we completely agree that OT is indeed a biomarker of disease activity, which has been shown in previous studies. [2][3][4][5] As Santos et al correctly point out, OT scores in the present study significantly differed already at baseline, that is, before disease-modifying therapy (DMT) initiation, between patients with and without treatment response. We also agree that, in line with previous studies, this is in all likelihood explained by the influence of recent disease activity.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 77%
“…Date received: 9 July 2022; revised: 14 July 2022; accepted: 14 July 2022 Dear Editor, Olfactory dysfunction has been studied in multiple sclerosis (MS). 1 We have recently read the paper by Bsteh et al, 2 stating that olfactory threshold (OT) predicts treatment response in relapsing multiple sclerosis (RMS). Absolute OT score (hazard ratio (HR) = 0.44, p < 0.001) and OT score improvement (HR = 0.12, p < 0.001) at 3 months after disease modifying treatment (DMT) initiation were associated with reduced relapse risk in the following 5 years.…”
Section: Olfactory Threshold As a Biomarker Of Disease Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis also affects the eyes, causing thinning of the nerve fiber layer (NFL), ganglion cell layer (GCL), inner plexiform layer (IPL) and inner nuclear layer (INL) of the retina, reduced macular volume and optic neuritis (Cennamo et al, 2016;Petzold et al, 2017;Pearson et al, 2022;Usta and Gunay, 2023;Vujosevic et al, 2023) (summarized in Figure 1). Therefore, retinal imaging biomarkers are a growing area of interest for early detection and monitoring of MS. Spectral domain OCT has emerged as a valuable tool for investigating neurodegeneration in the retina and has demonstrated that increased thinning of the inner retinal layers is associated with worsening long-term disability in MS (Lambe et al, 2021;Bsteh et al, 2023;Gernert et al, 2023). OCT studies have also revealed that atrophy of the retinal NFL and GCL reflect brain atrophy in MS patients, particularly grey matter loss (Saidha et al, 2015;Cagol et al, 2023).…”
Section: Retinal Imaging Biomarkers and Microglia In Msmentioning
confidence: 99%
“…concerning our manuscript ‘Olfactory threshold as a biomarker of disease activity’, we appreciate the interest in our work. 1…”
mentioning
confidence: 99%